2000
DOI: 10.1111/j.1574-6968.2000.tb08867.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal integration of the green fluorescent protein gene in lactic acid bacteria and the survival of marked strains in human gut simulations

Abstract: An integration vector was constructed to allow introduction of the gfp gene into the chromosomes of Gram-positive bacteria. Integration depends on homologous recombination between a short 458-nt sequence of the tet(M) gene in the vector and a copy of Tn916 in the host chromosome. Strains of Lactococcus lactis IL1403, Enterococcus faecalis JH2-SS, and Streptococcus gordonii DL1 stably marked with single chromosomal copies of the gfp were readily visualised by epifluorescence microscopy. The marked L. lactis str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Several other studies have reported on the successful use of homologous recombination for the stable integration of genes in bacterial genomes (38,49,50). Our results indicated that disruption or inactivation of the chromosomally located L. plantarum 423 dam gene was not lethal and had no impact on the strain's growth capacity.…”
Section: Discussionsupporting
confidence: 57%
“…Several other studies have reported on the successful use of homologous recombination for the stable integration of genes in bacterial genomes (38,49,50). Our results indicated that disruption or inactivation of the chromosomally located L. plantarum 423 dam gene was not lethal and had no impact on the strain's growth capacity.…”
Section: Discussionsupporting
confidence: 57%
“…However, imprecise repair of DSBs has the potential to be highly deleterious, as it can lead to genome instability, including the formation of chromosomal rearrangements. In particular, chromosomal translocations can arise when DNA ends from DSBs on two heterologous chromosomes are improperly joined (Scott et al, 2000). Given this, researchers have been taking advantage of various nucleases, especially the recently developed programmable nucleases, to deliberately induce DSBs at loci of interest to generate translocations.…”
Section: Introductionmentioning
confidence: 99%
“…Successful expression of GFP in different lactic acid bacteria has been reported from several laboratories [15] [16] [13]. The ability of streptococcal strains expressing GFP to survive in vivo and to be suitable for pathogenesis studies has been demonstrated for Streptococcus suis [15].…”
Section: Introductionmentioning
confidence: 99%